The particleboard made from kenaf and its properties / Mohamad Jani, S ... [et al.] - S, Mohamad Jani; S, Rahim; Koh, M.P; H, Norul hisham; B, Saimin; D, Muhammad; P, Nordin; S, Jalali (2004)
The development of particleboard from kenaf (Hibiscus cannabinus L., Malvaceae) was carried out. The kenaf core fiber with sizes 1-2 mm was used to produce homogeneous layer of particleboard with UF (urea formaldehyde) and PF (phenol formaldehyde) loading at 10% and 12%. Three series of target density of board were produced, i.e., 500, 600 and 700kg/m3 The board was evaluated based on its property performance via mechanical, dimensional stability as well as formaldehyde emission tests. The preliminary result indicated that the mechanical properties of board especially at density of 600-700 kg/m3 are comply with the EN 312-3 (1996) specification, which is suitable for interior fitments (including furniture) use in dry conditions. The study found that UF bonded board better of mechanical properties than PF-bonded board especially at 12% resin loading. Thickness swelling and formaldehyde emission tests were conducted where the results exhibit the low percentages and formaldehyde emission, respectively for board containing PF resin than UF resin.